Hindia Belanda dalam Fotografi - Prayanto Widyo Harsanto (Ars: Jurnal Seni Rupa dan Desain, 2011)
Netherlands East Indies in Photography. The Dutch colonization in Indonesia caused two different cultures- the Western culture (Europe-Dutch) and the Eastern culture (Indonesia) - to meet. Each was supported by distinct ethnic with dissimilar social structure as well. This situation resulted in the fact that the Dutch culture enriched the Eastern cultures, Javanese culture for instance. The Dutch culture influenced broader field and various culture elements. The Indies style was developed to cope with the historical, political, social, economical, art and cultural condition. The Indies style can be sensed in many forms of documentation, photography to mention one. Meanwhile, the need of visual information to be used in knowledge development and the tracing of human civilization became crucial. Basically, photography concerns with how this recording technology encourages the effort to study the need. This study aimed at proofing that photography in Netherlands East Indies was not merely a recording aid,but also an agent of modernization and of life style changes. It also illustrated how the Eastern image was projected by the Western (Orientalism)Keywords: photography, Indies culture, Orientalism